Efeito da ovariectomia em novilhas Nelore x Angus, Bos taurus indicus x Bos taurus taurus sobre os ganhos de peso - Chacur, Marcelo George Mungai; Marin, Mauricio de Faria; Oba, Eunice [UNESP]; Kronka, Sergio do Nascimento (Universidade Estadual de Londrina (UEL), 2007)
This study aimed to evaluate the weight gain in cross breed heifers Nelore X Angus, spayed and nonspayed, kept on pasture and confinement. The animals were allotted in two groups as follows: group I consisted of 30 nonspayed heifers with 18 months old. Group 2 was composed of 30 spayed heifers with 18 months old. The animals were allotted in pasture of Brachiaria decumbens and weighted at 39 and 75 days. Significant difference was observed between the average daily gain of the two groups - G1 and G2 (75(th) day), respectively (0.51 kg and 0.65 kg; P<0.0 1). The following day (761 day), all animals were allotted and kept on confinement during 144 days. Significant difference was observed between the average daily gain of the two groups - G I and G2 (1441 day), respectively (0.73 kg and 0.58 kg; P<0.0 1). The results of this experiment show that spayed heifers presented a higher daily gain on pasture.
Ovariectomy effect in heifers Nelore x Angus, Bos taurus indicus x Bos taurus taurus on the weight gains
Keywords: beef cattle; castration; pasture; confinement